2006
DOI: 10.1007/s00441-006-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous delivery of a monoclonal antibody against Reissner’s fiber into CSF reveals CSF-soluble material immunorelated to the subcommissural organ in early chick embryos

Abstract: The subcommissural organ (SCO) is an ependymal differentiation located in the dorsal midline of the caudal diencephalon under the posterior commissure. SCO cells synthesize and release glycoproteins into the cerebrospinal fluid (CSF) forming a threadlike structure known as Reissner's fiber (RF), which runs caudally along the ventricular cavities and the central canal of the spinal cord. Numerous monoclonal antibodies have been raised against bovine RF and the secretory material of the SCO. For this study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…The results show that at HH23 (fourth day of development) the anti SCO-spondin recognizes four bands of 175, 140, 65, and 50 kDa; while at later stages additional bands of 350, 300, and 200 kDa appear, which is in agreement with previous reports (Hoyo-Becerra et al, 2006; Vio et al, 2008). Similar bands are found in the conditioned medium from HH36 SCO explants, with the exception of the smaller bands of 65 and 50 KDa (Figure 2, CM lane).…”
Section: Resultssupporting
confidence: 93%
“…The results show that at HH23 (fourth day of development) the anti SCO-spondin recognizes four bands of 175, 140, 65, and 50 kDa; while at later stages additional bands of 350, 300, and 200 kDa appear, which is in agreement with previous reports (Hoyo-Becerra et al, 2006; Vio et al, 2008). Similar bands are found in the conditioned medium from HH36 SCO explants, with the exception of the smaller bands of 65 and 50 KDa (Figure 2, CM lane).…”
Section: Resultssupporting
confidence: 93%
“…Based on these studies, we may assume that part of the luminal substance is glycidic. Cells specialized in the synthesis and secretion of glycoproteins that are released into the CSF are located in the subcommissural organ (SCO) of developing chickens, an ependymal differentiation located in the roof plate of the diencephalon [47], [48]. It has been proposed that the SCO secretion participates in ontogenetic processes in the CNS, such as neuronal differentiation, neuronal aggregation and axonal pathfinding [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Meiniel and coworkers (2003) have suggested that "SCO-spondin may display multifunctional activities during CNS development, involving different domains of the molecule, and according to the target cell type". Regarding the onset of the secretory activity of the chick SCO, a previous report by our group (Hoyo-Becerra et al 2006) has presented evidence suggesting that the SCO releases AFRU-positive material into the CSF at early stages of development (E5); however, that report contains no studies of earlier stages of development and so we can suspect, but not be certain, of SCO-spondin release at E4.…”
Section: Sco-spondin As a Putative Axonal Guidance Molecule In Sco Exmentioning
confidence: 93%
“…The sections were hydrated, rinsed with phosphate-buffered saline (PBS) with 0.05% Tween-20 (Sigma) and incubated in the primary antibody for 18 h at room temperature. The primary antibodies used in this study were: (1) a rabbit polyclonal antiserum against bovine RF (AFRU, 1:1000; Rodriguez et al 1984) kindly provided by Prof. Rodriguez (Valdivia, Chile; this antiserum recognizes chick SCO secretory material and has been previously used to study the development of chick embryo; Schoebitz et al 1986); (2) a mouse polyclonal antibody against bovine RF raised in our laboratory (AFRA; Hoyo-Becerra et al 2006); (3) a rabbit polyclonal antibody against Ng cell adhesion molecule (Ng-CAM; kindly provided by Dr. de la Rosa, Madrid, Spain); (4) a monoclonal antibody against β-III tubulin (Sigma).…”
Section: Collection Of Embryos Histology and Immunocytochemistrymentioning
confidence: 99%